2020
DOI: 10.3390/pathogens9110861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taenia Pisiformis Infection and Obesity on Clinical Parameters, Organometry and Fat Distribution in Male Rabbits

Abstract: Taenia pisiformis infection causes important economic loss in farms. It is suggested that obesity has a major impact on infection and reproduction. We addressed the impact of T. pisiformis infection in normal and obese rabbits to evaluate its effect on parameters important in behavior and reproduction. T. pisiformis infection in obese rabbits decreased body weight. In the obese-infected rabbits, eosinophils and heterophiles were increased 23% by the infection (P ≤ 0.05). T. pisiformis decreased cholesterol by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It is well known that T. pisiformis is a typical parasite of lagomorphs, especially rabbits and hares [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 19 , 20 , 21 ]. To date, this parasite has mostly been examined using the traditional detection method—identification of the macroscopic characteristics of the cysticercus and diagnosis by host specificity after autopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that T. pisiformis is a typical parasite of lagomorphs, especially rabbits and hares [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 19 , 20 , 21 ]. To date, this parasite has mostly been examined using the traditional detection method—identification of the macroscopic characteristics of the cysticercus and diagnosis by host specificity after autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Hallal-Calleros et al [ 21 ] observed a loss of fertility in rabbits suffering from T. pisiformis cysticercosis, and Alzaga et al [ 19 ] noted its negative relationship to kidney fat in the Iberian hare. Arias-Hernandez et al [ 20 ] showed that rabbits infected with this parasite have modified metabolic characteristics (e.g., lipid metabolism), which may affect production and animal welfare. Moreover, in the case of obesity, these changes are intensified.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that Schistosoma mansoni ( S. mansoni ) infection improves glucose tolerance, body mass and liver steatosis in HFD mice but aggravates pathological damage to the liver in mice ( 98 ). Similarly, Taenia pisiformis infection decreases body weight and cholesterol level in obese rabbits and changes the metabolic features in rabbits ( 99 ). Bhargava et al.…”
Section: Pathogenesis Of Nafldmentioning
confidence: 99%
“…Most reports on helminth regulation of NAFLD-related diseases, including obesity, T2DM, and MetS, focused on nematodes and trematodes, such as N. brasiliensis , H. polygyrus , L. sigmodontis , S. venezuelensis , S. mansoni , and S. japonicum ( 95 ). In the case of cestodes, only T. pisiformis interventions were seen in obese rabbits ( 99 ). In addition, ESPs from larval E. granulosus can reverse HF-induced gut barrier dysfunction and microbiota dysbiosis, thereby protecting against obesity-associated neurodegenerative diseases ( 133 ).…”
Section: Challenges and Prospectmentioning
confidence: 99%
“…In China, T. pisiformis has also been reported [6]. Once infected with C. pisiformis, rabbits will show decreased prolificacy, weight loss and weakened immunological resistance, causing serious economic losses to the rabbit breeding industry [7,8]. The Dot-ELISA diagnostic method has been reported for detection of C. pisiformis, but has high false positive rate limit applicability [9].…”
Section: Introductionmentioning
confidence: 99%